ChemInform Abstract: Rh‐Catalyzed Direct Cyclization of 1, 4‐Naphthoquinone and 9, 10‐Phenanthraquinone with Alkyne: Facile Access to 1, 8‐Dioxapyrenes and 1, 12‐Dioxaperylenes as Orange and Red‐Emitting Luminophores. Issue 32 (August 2015) - Wang, Jing; Qin, Dekun; Lan, Jingbo; Cheng, Yangyang; Zhang, Shuai; Guo, Qiang; Wu, Jie; Wu, Di; You, Jingsong
Abstract A facile and efficient method for the synthesis of 1, 8‐dioxapyrenes and 1, 12‐dioxaperylenes through Rh‐catalyzed direct cyclization of 1, 4‐naphthoquinones and 9, 10‐phenanthraquinones with alkynes is developed.